Heterogenous bone response to biologic DMARD therapies in rheumatoid arthritis patients and their relationship to functional indices - Brunet, S. C.; Tse, J. J.; Kuczynski, M. T.; Engelke, Klaus; Boyd, S. K.; Barnabe, C.; Manske, S. L. (Scandinavian Journal of Rheumatology, 2021)
Objectives: Previous studies of high-resolution peripheral quantitative computed tomography (HR-pQCT) imaging of hand joints in patients with rheumatoid arthritis (RA) have suggested that erosion healing may occur. Our objective was to examine changes in erosion volume, joint space width (JSW), bone mineral density (BMD), and bone remodelling, and their association with clinical outcomes and measures of patient hand function. Method: We examined 48 patients who achieved a good response to a newly initiated biologic therapy. HR-pQCT images of the dominant hands’ second and third metacarpophalangeal joints were obtained 3 and 12 months after therapy initiation. Bone erosion volume, JSW, BMD, and bone remodelling were quantified from HR-pQCT images, with improvement, no change (unchanged), or progression in these measures determined by least significant change. Disease activity and hand function measures were collected. Results: There were no significant group changes in HR-pQCT outcomes over the 9 month period. Twenty-two patients had total erosion volumes that remained unchanged, nine showed improvement, and two progressed. The majority of JSW and BMD measures remained unchanged. There was a significant association between the baseline Health Assessment Questionnaire score and the change in minimum JSW, but no other significant associations between HR-pQCT outcomes and function were observed. Conclusions: The vast majority of patients maintained unchanged JSW and BMD over the course of follow-up. Significant improvements in total erosion volume occurred in 27% of patients, suggesting that biologic therapies may lead to erosion healing in some patients, although this did not have an impact on self-reported and demonstrated hand function.
CRIS-Team Scopus Importer:2021-04-09